Italian culture
Covers the broad and diverse interests of the Association's members, offering scholarly articles in Italian language, linguistics, history, literature, cinema, politics, philosophy, folklore, popular culture, migration, and the influence of Italy on other cultures. It also includes articles in comparative literature and cultural studies.